Field varietal screening against African rice gall midge: IITA research guide, No. 34 - Okocha, P.; Ukwungwu, M.N.; Joshi, R. (1994)
The African rice gall midge (ARGM) is an insect pest of rice in Africa which has recently attained outbreak levels in many African countries. Infestation can result in total crop failure. The use of insecticides to control the pest has several disadvantages. Cultivation of resistant varieties is the best control method. However, resistance is location specific. Screening for resistance over three to four year at the same location helps to identify resistant varieties for use by farmers.